Farmers’ Adoption of Agricultural Innovations: A Systematic Review on Willingness to Pay Studies - Olum, Solomon; Gellynck, Xavier; Juvinal, Joel; Ongeng, Duncan; Steur, Hans De (Outlook on Agriculture, 2020)
Unlike most studies that focused on specific innovations, this study systematically analyzed farmers’ adoption of agricultural innovations in general. It reports willingness to pay (WTP; willingness to accept (WTA)) as a proxy for adoption, its determinants, applied methods, and statistical models. After searching and screening, 80 studies qualified for review. Majority (n = 30) of studies focused on farmers’ WTP for innovations in agricultural water provision or environmental and crop protection (n = 35), while the remaining studies handled crop or animal improvement innovations. Most studies were performed in developing countries, using stated preference methods for economic valuation, with 55% of the studies (n = 44) applying contingent valuation compared to 39% taking choice modeling approach. While farmers are generally willing to pay premium for improvement in agriculture technologies, WTP (WTA) depends on the innovation (system). For example, premiums ranged from about 0.125 to 2 USD/m3 of water depending on water supply (e.g. ground vs. surface water). Furthermore, the determinants of farmers’ WTP can be grouped into sociodemographic, biophysical, technological, institutional, and behavioral factors. As illustrated by relatively high WTP, the review demonstrates that farmers embrace most innovations, regardless of the context and methods applied.
Keywords: Agricultural innovations, economic valuation, premium, willingness to accept, willingness to pay